2018
DOI: 10.1080/15476278.2018.1462433
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol enhances Atoh1 expression in inner ear stem cells and promotes their differentiation into functional auditory neuronal-like cells

Abstract: We aimed to investigate the beneficial effect of Celastrol on inner ear stem cells and potential therapeutic value for hearing loss. The inner ear stem cells were isolated and characterized from utricular sensory epithelium of adult mice. The stemness was evaluated by sphere formation assay. The relative expressions of Atoh1, MAP-2 and Myosin VI were measured by RT-PCR and immunoblotting. The up-regulation of MAP-2 was also analysed with immunofluorescence. The in vitro neuronal excitability was interrogated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Recent studies have shown that celastrol can significantly increases the activity and proliferation of inner ear stem cells, stimulates the differentiation of inner ear stem cells into neuron-like cells, and enhances neural excitability and electrophysiological activity. These results may be associated with the upregulation of the Atoh1 gene, an important positive regulator of sensory cell differentiation in the inner ear [ 179 ]. However, due to high level of toxicity of Tripterygium wilfordii Hook.…”
Section: Herbal Medicines For Hearing Lossmentioning
confidence: 99%
“…Recent studies have shown that celastrol can significantly increases the activity and proliferation of inner ear stem cells, stimulates the differentiation of inner ear stem cells into neuron-like cells, and enhances neural excitability and electrophysiological activity. These results may be associated with the upregulation of the Atoh1 gene, an important positive regulator of sensory cell differentiation in the inner ear [ 179 ]. However, due to high level of toxicity of Tripterygium wilfordii Hook.…”
Section: Herbal Medicines For Hearing Lossmentioning
confidence: 99%
“…The target cells used for auditory cell production are mainly stem cells, such as bone marrow-derived mesenchymal stem cells [11], neural stem cells [12], embryonic stem cells [13], and induced pluripotent stem cells [14]. In recent years, several studies have showed that the stem cells derived from mammalian inner ear, which nominated inner ear stem cells, have potential to differentiate into hair cells, supporting cells under certain induction conditions [15][16][17]. Generally, stem cell differentiation is greatly influenced by the cellular and tissue microenvironment in vivo [18].…”
Section: Introductionmentioning
confidence: 99%